Assessment of dietary knowledge, lifestyle and management of long-duration type 2 diabetes in middle-aged adults (55-65 years) residing in Mumbai city: a cross-sectional study - Hema Goenka; Reema Mathur (International Journal Of Community Medicine And Public Health, 2026)
Background: Type 2 Diabetes Mellitus (T2DM) is a major public health problem in India. Dietary knowledge and self-management are important for effective diabetes management, yet adherence to recommended dietary practices may remain suboptimal in individuals with long-duration disease. This study assessed lifestyle, dietary knowledge and management practices among middle-aged adults with long-duration T2DM attending a tertiary care hospital in Mumbai. Methods: An observational cross-sectional study was conducted among 75 participants aged 55-65 years with T2DM for more than five years. Data were collected from January 2023 to February 2023 using a structured interview schedule covering sociodemographic profile, lifestyle, medical management, and dietary knowledge and management. Data were analyzed using SPSS version 25, and descriptive statistics were computed. Results: Most participants (97.3%) recognized that diet influences diabetes. Awareness of the My Plate Method was 60.0%, while 50.7% recognized low-carbohydrate diets as a management approach. Carbohydrates were correctly identified as the macronutrient most affecting blood glucose by 82.7% of participants. However, 34.6% were unaware of established dietary frameworks, 18.7% considered jaggery a safer sweetener, and 53.3% selected farsan as an appropriate snack. Medication adherence was high (90.4%), while 34.7% reported no physical exercise. Despite good dietary knowledge, practices remained inconsistent with recommendations. Conclusions: A substantial knowledge-to-practice gap was observed among middle-aged adults with long-duration T2DM. Structured, individualized and culturally sensitive dietary counselling, reinforced through regular follow-up, is needed to improve dietary self-management.